Author Correction: Discovery of small molecule inhibitors of MyD88-dependent signaling pathways using a computational screen. Issue 1 (December 2018) - Olson, Mark; Lee, Michael; Kissner, Teri; Alam, Shahabuddin; Waugh, David; Saikh, Kamal
A correction has been published and is appended to both the HTML and PDF versions of this paper. The error has not been fixed in the paper.